The abolition of poverty - Horowitz, David (New York : Praeger Publishers, 1969)
This book deals with the most crucial problem of the twentieth century: the existence of poverty in the midst of plenty. The widening gap between the standards of living of the developed and underdeveloped nations, the clash and conflict in the cities of some of the affluent nations, and the tragic implications of both situations for the peace of the world provide the motivation for an analysis of ways to eliminate poverty once and for all.
Bibliography: p. 173-178
osa;14/7/17
Loans
Keywords: Economic development; Developing countries- Economic conditions